Biomechanical properties of bone are impaired in patients with ACPA-positive rheumatoid arthritis and associated with the occurrence of fractures. Issue 7 (23rd February 2018) - Stemmler, Fabian; Simon, David; Liphardt, Anna-Maria; Englbrecht, Matthias; Rech, Juergen; Hueber, Axel J; Engelke, Klaus; Schett, Georg; Kleyer, Arnd
Abstract : Objectives: Bone loss is a well-established consequence of rheumatoid arthritis (RA). To date, bone disease in RA is exclusively characterised by bone density measurements, while the functional properties of bone in RA are undefined. This study aimed to define the impact of RA on the functional properties of bone, such as failure load and stiffness. Methods: Micro-finite element analysis (µFEA) was carried out to measure failure load and stiffness of bone based on high-resolution peripheral quantitative CT data from the distal radius of anti-citrullinated protein antibody (ACPA)-positive RA (RA+), ACPA-negative RA (RA−) and healthy controls (HC). In addition, total, trabecular and cortical bone densities as well as microstructural parameters of bone were recorded. Correlations and multivariate models were used to determine the role of demographic, disease-specific and structural data of bone strength as well as its relation to prevalent fractures. Results: 276 individuals were analysed. Failure load and stiffness (both P<0.001) of bone were decreased in RA+, but not RA−, compared with HC. Lower bone strength affected both female and male patients with RA+, was related to longer disease duration and significantly (stiffness P=0.020; failure load P=0.012) associated with the occurrence of osteoporotic fractures. Impaired bone strength was correlated with altered bone density and microstructural parameters, which were all decreased in RA+. Multivariate models showed that ACPA status (P=0.007) and sex (P<0.001) were independently associated with reduced biomechanical properties of bone in RA. Conclusion: In summary, µFEA showed that bone strength is significantly decreased in RA+ and associated with fractures.